PD-1 is expressed in cytotoxic granules of NK cells and rapidly mobilized to the cell membrane following recognition of tumor cells - Cecilia Pesini; Sandra Hidalgo; Maykel A. Arias; Llipsy Santiago; Carlota Calvo; Maitane Ocariz-Díez; Dolores Isla; Pilar M. Lanuza; M José Agustín; Eva M Galvez; Ariel Ramírez-Labrada; Julián Pardo (OncoImmunology)
The contribution of the T cell-related inhibitory checkpoint PD-1 to the regulation of NK cell activity is still not clear with contradictory results concerning its expression and role in the modulation of NK cell cytotoxicity. We provide novel key findings on the mechanism involved in the regulation of PD-1 expression on NK cell membrane and its functional consequences for the elimination of cancer cells. In contrast to freshly isolated NK cells from cancer patients, those from healthy donors did not express PD-1 on the cell membrane. However, when healthy NK cells were incubated with tumor target cells, membrane PD-1 expression increased, concurrent with the CD107a surface mobilization. This finding suggested that PD-1 was translocated to the cell membrane during NK cell degranulation after contact with target cells. Indeed, cytosolic PD-1 was expressed in freshly-isolated-NK cells and partly co-localized with CD107a and GzmB, confirming that membrane PD-1 corresponded to a pool of preformed PD-1. Moreover, NK cells that had mobilized PD-1 to the cell membrane presented a significantly reduced anti-tumor activity on PD-L1-expressing-tumor cells in vitro and in vivo, which was partly reversed by using anti-PD-1 blocking antibodies. Our results indicate that NK cells from healthy individuals express cytotoxic granule-associated PD-1, which is rapidly mobilized to the cell membrane after interaction with tumor target cells. This novel finding helps to understand how PD-1 expression is regulated on NK cell membrane and the functional consequences of this expression during the elimination of tumor cells, which will help to design more efficient NK cell-based cancer immunotherapies.